Conocimientos profesionales de los profesores - Bromme, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Strangely enough, professional knowledge of teachers has been rarely studied so far. This paper presents starting points for this subject and possible open lines for research are suggested.